2022
DOI: 10.30574/gscarr.2022.10.3.0064
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical determination of reduced glutathione concentration in pig liver and kidney in the presence of chlorinated aquatic humic materials

Abstract: Disinfection of surface waters for human consumption and use often results in reaction between the disinfectant (generally chlorine) and organic substrates present at the source. These substrates are majorly in the form of aquatic humic materials. This work was designed to assess reduced glutathione (GSH) concentration in pig liver and kidney in the presence of chlorinated aquatic humic materials (CAHMs) using biochemical parameters. GSH concentration in pig liver and kidney was investigated following standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Red blood cell G6PD value of >2.9 U/gHb was regarded as normal, while those with red blood cell G6PD value of <2.9 U/gHb were regarded as deficient and those with red blood cell G6PD value of <1.6 U/gHb were regarded as severely deficient (Isaac et al, 2013). GSH was measured using standard procedure https://doi.org/ 10.57233/ijsgs.v9i4.543 URL: https://fugus-ijsgs.com.ng Principle: The principle is based on the reduction of 5,5'dithiobis (2-nitrobenzoic acid) (DTNB) with reduced glutathione (GSH) to produce 2nitro-5-mercapto-benzoic acid (TNB), which possesses its absorption maximum at 412nm (Nse et al, 2022). GSH concentration was calculated using the formula:…”
Section: Materials and Methods 21 Study Areamentioning
confidence: 99%
“…Red blood cell G6PD value of >2.9 U/gHb was regarded as normal, while those with red blood cell G6PD value of <2.9 U/gHb were regarded as deficient and those with red blood cell G6PD value of <1.6 U/gHb were regarded as severely deficient (Isaac et al, 2013). GSH was measured using standard procedure https://doi.org/ 10.57233/ijsgs.v9i4.543 URL: https://fugus-ijsgs.com.ng Principle: The principle is based on the reduction of 5,5'dithiobis (2-nitrobenzoic acid) (DTNB) with reduced glutathione (GSH) to produce 2nitro-5-mercapto-benzoic acid (TNB), which possesses its absorption maximum at 412nm (Nse et al, 2022). GSH concentration was calculated using the formula:…”
Section: Materials and Methods 21 Study Areamentioning
confidence: 99%
“…Islam, et al [35]; Abdi-Hachesoo, et al [36] reported a RBC range (2.9 -3.5 10 6 /µl), this variation could simply be as a result of differences in age, sex, breed, environment, hormones and nutrition [37]. Haematological indices are used to in disease diagnosis as well as extent of damage to the blood [38,39]. PCV and MCH are useful indices for the diagnosis of anaemia Nse Abasi, et al [38]; Alagbe [13].…”
Section: Methodsmentioning
confidence: 99%
“…Haematological indices are used to in disease diagnosis as well as extent of damage to the blood [38,39]. PCV and MCH are useful indices for the diagnosis of anaemia Nse Abasi, et al [38]; Alagbe [13]. A higher RBC level is an indication of adequate oxygen in the blood which gives room for effective nutrient transportation in the body [40,41].…”
Section: Methodsmentioning
confidence: 99%